Succession Politics and Power-sharing in Nigeria - ORJI, Nkwachukwu (Socialscientia: Journal of Social Sciences and Humanities, 2022)
This article examines the relationship between succession politics and power sharing. It argues that existing literature on the subject overlook recent and significant developments, especially the push for peaceful political succession in Africa through the process of power sharing. While acknowledging that succession politics is a major source of conflicts in Africa, especially within the context of ethnic diversity, economic underdevelopment, and strong ethno-political rivalry, the article contends that a major feature of succession politics in Nigeria is the search for orderly regime change. This search has culminated in the establishment of power-sharing arrangements. While power-sharing appears critical in eliminating political uncertainty and moderating the behaviour of political actors, it has fueled succession related conflicts by eliminating the competitiveness that leads to alternation of power among political parties. This, in turn, has facilitated one-party dominance and imposition of successors by incumbents and other political “godfathers”.